(3GdfGaY jhe GdMTQ aj TQM GdHGH GdMGOj YTQs - (3GdSjhQj, GdMdj, GdCSOj, CHh YHO Gddg, TQa GdOjf, ebOGO Hf YHO Gddg Hf eMeO Hf GdMSjf, J (B826s
(3ChdgG (B:s
(3GdMeO ddg (B... (3aef Jdc GdebOeGJ GdebOeI GdehSheI HGdHGH GdMGOj YTQ GdfGaY aj jhe GdMTQ ef JUGfja TjNfG (B... (3CHj efUhQ GdMSf Hf GdeWgQ (B.. (3aCfgG eY hLGRI daXgG cKjQI GdYde heY GNJUGQ JbQjQgG cKjQI GdZfe hcGf bO Sda ef SGda GdReGf Cf cJHJ TjFG jYjf Ydi MdgG (B..s
(3BNQgG (B:s
... (3ef GdVQ GdMGUd HSHH GdCeQ Ch Gdfgj EeG EdjgeG Ch dCMO ef GdeSdejf aGf ZdH YfOgeG MUhd Pdc GQJaY GdhLhH CjVG hjLHGf HGdbdH hGddSGf hGdjO hdG jfJbd Edi GdCUYH eY GfLGM GdCSgd agPG eG JgjA dj JJejeg hcJGHJgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\ 2828s
(3GdPQjYI (B24 \ 13 ( 94)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds